2017
DOI: 10.1007/s00248-017-1021-z
|View full text |Cite
|
Sign up to set email alerts
|

Variation of Synechococcus Pigment Genetic Diversity Along Two Turbidity Gradients in the China Seas

Abstract: Synechococcus are important and widely distributed picocyanobacteria that encompass a high pigment diversity. In this study, we developed a primer set (peBF/peAR) for amplifying the cpeBA operon sequence from Synechococcus genomic DNA to study Synechococcus pigment diversity along two turbidity gradients in the China seas. Our data revealed that all previously reported pigment types occurred in the South (SCS) and East (ECS) China Seas. In addition, a novel pigment genetic type (type 3f), represented by the hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(43 citation statements)
references
References 39 publications
2
41
0
Order By: Relevance
“…These results are in agreement with the prevailing view of an increase in the PUB:PEB ratio from green onshore mesotrophic waters to blue offshore oligotrophic waters (19-24, 26-29, 40, 48). Similarly, we showed that PT 3dB, which could not be distinguished from PT 3c in previous studies (17,(29)(30)(31), prevails in more coastal and/or mixed temperate waters than do 3c populations. The realized environmental niche of the second type of CA4 (PT 3dA) is the best defined of all PTs as it is clearly associated with nutrient-rich waters and with the coldest stations of our dataset, occurring at high latitude, at depth, and/or in vertically mixed waters (e.g., TARA_068, 093, and 133).…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…These results are in agreement with the prevailing view of an increase in the PUB:PEB ratio from green onshore mesotrophic waters to blue offshore oligotrophic waters (19-24, 26-29, 40, 48). Similarly, we showed that PT 3dB, which could not be distinguished from PT 3c in previous studies (17,(29)(30)(31), prevails in more coastal and/or mixed temperate waters than do 3c populations. The realized environmental niche of the second type of CA4 (PT 3dA) is the best defined of all PTs as it is clearly associated with nutrient-rich waters and with the coldest stations of our dataset, occurring at high latitude, at depth, and/or in vertically mixed waters (e.g., TARA_068, 093, and 133).…”
Section: Discussionsupporting
confidence: 78%
“…Marine Synechococcus display a large pigment diversity, with different PTs preferentially harvesting distinct regions of the light spectrum. Previous studies based on optical properties or on a single genetic marker could not differentiate all PTs (17,(29)(30)(31), and thus neither assess their respective realized environmental niches (43) nor the role of light quality on the relative abundance of each PT. Here, we showed that a metagenomic read recruitment approach combining three genetic markers can be used to reliably predict all major PTs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This ecological success is tied to the remarkably large genetic (Ahlgren and Rocap 2012;Huang et al 2012;Mazard et al 2012;Farrant et al 2016) and pigment diversity exhibited by these cells (Six et al 2007;Humily et al 2013;Grébert et al 2018;Xia et al 2018). The pigment diversity arises from wide variations in the composition of their light-harvesting antennae, called phycobilisomes (PBS).…”
Section: Introductionmentioning
confidence: 99%
“…Gene content analysis identified these as a new PT 2 genotype named PT 2B, while the original PT 2 was renamed PT 2A. Finally, the genome sequencing of the high-PUB-containing strains KORDI-100 and CC9616 showed that although they display a high, PT 3c-like Exc495:545 ratio, the gene complement, order, and alleles of their PBS rod region differ from PT 3c, establishing an additional pigment subtype called PT 3f (Mahmoud et al 2017;Grébert et al 2018;Xia et al 2018). An interesting feature of the genes within the PBS rod region is that their evolutionary history apparently differs from that of the core genome (Six et al 2007;Everroad and Wood 2012;Humily et al 2014;Grébert et al 2018;), but the reason(s) for this autonomy remains unclear.…”
Section: Introductionmentioning
confidence: 99%